Organizational commitment among employees : the case study of Tenaga Nasional Berhad [TNB] Kulim / Nur Asilah Mohd Zubir - Mohd Zubir, Nur Asilah (2019)
Nowadays, organizational commitment among employees becomes an important thing in the organization. According to Palmiano (2017), organizational commitment can be defined as an attitude about staffs’ faithfulness towards the organization and it is a practice where the members of organization show their interest in organization and towards the success and efficiency of the organization. The main objective of this study is to investigate the influence of organizational commitment among employees in the organization. The dependent variable is organizational commitment while the independent variable is employee empowerment, teamwork, employee training, leadership style and work specialization. Census was used in this study. The opulation of this study was 150 employees from Tenaga Nasional Berhad (TNB) Kulim and there are 145 respondents who responded to the questionnaires which includes from 14 units in the organization. In this study, there are 73 items of questionnaires using five point Likert scale. There is some statistical technique were used such as frequency analysis, factor analysis, descriptive analysis, reliability analysis, Pearson’s correlation analysis and regression analysis. In this study, the researcher had found that teamwork, leadership style and work specialization were positively related with organizational commitment but employee empowerment and employee training had found negatively related with organizational commitment